Educating the always-on generation in an instant(gram) #blendedlearning - Swanepoel, G. P.; Bruwer, A. (University of the Free State, 2020)
The anticipated Fourth Industrial Revolution and the non-linear sharing of information have afforded tertiary education institutions with opportunities to apply new technology to their pedagogy model. The prominence of social networking sites (SNSs), specifically Instagram, calls for educational institutions to innovate and acknowledge, as well as apply, these SNSs within an innovative blended learning approach. This study aimed to analyse students’ perspectives on the use of Instagram as a blended learning educational and administrative tool in tertiary education. While the use of Facebook as an educational tool is widely researched, limited studies exist on the use of Instagram in tertiary education. The expectation is therefore set on tertiary education to apply Instagram for effective communication and an enhanced teaching experience. The Instagram account created by the research team as a blended learning tool had more than 270 student followers. Their perceptions of the use of Instagram in tertiary education were evaluated using a questionnaire approach and analysed as continuous data on a five-point Likert scale. By using a one-way t-test, the preferred blended learning approach to be implemented on Instagram was determined. Open-ended questions were asked to obtain a better understanding of what students expect and prefer from the use of SNSs, specifically Instagram, in tertiary education. While previous research only focused on the possibility of the implementation of Instagram and the use of videos on Instagram, this study indicates how tertiary education can apply the various functions of Instagram within an innovative blended learning approach. The study found that Instagram creates an always-on learner, who thinks about the module outside of lectures. Students perceive it as an effective educational tool in aiding them to understand difficult topics better, as well as an administrative tool that complements the current administrative systems. The overall perception was concluded to be that Instagram is welcome in tertiary education, with both the lecturer and the student as the driving force.
Keywords: Instagram; Technology; Tertiary education; Blended learning; iGeneration; Always-on learning